The relationship between firm size, asset tangibility, and retained earnings on financial leverage of firms listed in Bursa Malaysia / Angelle Shazlina Samsudin - Samsudin, Angelle Shazlina (2017)
The aim of this study is to examine the relationship of firm size, asset tangibility and retained earnings on financial leverage of firms listed in Bursa Malaysia. The study is based on secondary data collected from Thomson-Reuters data stream based on yearly basis for 5 years starting from period 2010 to 2014. The regression method used is panel data component of 5 years. Independent variables are firm size, asset tangibility, and retained earnings, while the dependent variable is financial leverage. Overall result shows that firm size has positive but insignificant relationship on financial leverage, while the asset tangibility also has positive relation but is significant towards financial leverage. Retained Earnings on the other hand shows that it has negative correlation but significant relationship on financial leverage.